2007
DOI: 10.2136/sssaj2005.0212
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching from Kentucky Bluegrass Soil Columns Predicted with Anion Exchange Membranes

Abstract: Ideal nitrogen (N) management for turfgrass supplies sufficient N for high‐quality turf without increasing N leaching losses. A greenhouse study was conducted during two 27‐wk periods to determine if in situ anion exchange membranes (AEMs) could predict nitrate (NO3–N) leaching from a Kentucky bluegrass (Poa pratensis L.) turf grown on intact soil columns. Treatments consisted of 16 rates of N fertilization, from 0 to 98 kg N ha−1 mo−1 Percolate water was collected weekly and analyzed for NO3–N. Mean flow‐weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Fertilizers used with the application timings in this study were effective at reducing the potential for N leaching. Barry et al (2009) and Magniafico and Guillard (2007) reported that monthly IEM-N below 44 to 81 µg NO 3 -N cm -2 28 d -1 resulted in non-significant or below drinking water contamination amounts of N leaching, respectively. The greatest IEM-N in this study was 12.8 µg (NO 3 -+ NH 4 + )-N cm -2 28 d -1 , which is well below the concentration breakpoint related to N leaching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizers used with the application timings in this study were effective at reducing the potential for N leaching. Barry et al (2009) and Magniafico and Guillard (2007) reported that monthly IEM-N below 44 to 81 µg NO 3 -N cm -2 28 d -1 resulted in non-significant or below drinking water contamination amounts of N leaching, respectively. The greatest IEM-N in this study was 12.8 µg (NO 3 -+ NH 4 + )-N cm -2 28 d -1 , which is well below the concentration breakpoint related to N leaching.…”
Section: Resultsmentioning
confidence: 99%
“…Ion exchange membranes (IEM) and mesh bag techniques have been used to determine the amount of plant‐available N and the N release (NR) rate from EEFs. In turfgrass, NO 3 – captured on anion exchange membranes correlated with visual quality and color ratings, clipping yield, N uptake, and N leaching (Barry et al., 2009; Kopp & Guillard, 2002; Mangiafico & Guillard, 2005, 2006, 2007). Field experiments have been conducted using the mesh bag technique to determine NR characteristics, potassium released from EEFs, and coated fertilizer prill integrity and NR under traffic (Cheng, 2017; Synder & Cisar, 1992; Wilson et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Soil conditions and differences in root morphology and/or architecture may played a more important role than root uptake capacity in determining No 3 leaching from these Kentucky bluegrass genotypes. Roy et al, 2000;Snyder et al, 1984;Starr and DeRoo, 1981), heavy or mistimed fertilization (Brown et al, 1977(Brown et al, , 1982Guillard and Kopp, 2004;Mangiafico and Guillard, 2007;Petrovic et al, 1986;Rieke and Ellis, 1974;Roy et al, 2000;Sheard et al, 1985;Snyder et al, 1981), sandy soils (Brown et al, 1982;Petrovic, 1990;Rieke and Ellis, 1974), and mature turf (Frank et al, 2006;Petrovic, 1990;Porter et al, 1980). The low potential for NO 3 leaching in turfgrass is often attributed in large part to efficient N uptake by roots (Bowman et al, 1989b;Morton et al, 1988;Petrovic, 1990).…”
Section: Nitrate Leaching From Two Kentucky Bluegrass Cultivars As Afmentioning
confidence: 99%
“…Roy et al, 2000;Snyder et al, 1984;Starr and DeRoo, 1981), heavy or mistimed fertilization (Brown et al, 1977(Brown et al, , 1982Guillard and Kopp, 2004;Mangiafico and Guillard, 2007;Petrovic et al, 1986;Rieke and Ellis, 1974;Roy et al, 2000;Sheard et al, 1985;Snyder et al, 1981), sandy soils (Brown et al, 1982;Petrovic, 1990;Rieke and Ellis, 1974), and mature turf (Frank et al, 2006;Petrovic, 1990;Porter et al, 1980). This column lysimeter study was conducted to examine No 3 leaching from two Kentucky bluegrass (Poa pratensis L.) cultivars differing in No 3 uptake capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Shade from trees can also weaken the turfgrass beneath it, reducing root competition. Since irrigation rate, nitrogen source and rate, grass species and vigor, season, and soil type can all influence nitrogen leaching rates in turfgrass systems (Petrovic 1990) amounts of nitrogen leached can vary widely from less than 1% to 71% of that applied (Petrovic 1990;Guillard and Kopp 2004;Barton and Colmer 2005;Paré et al 2006;Mangiafico 2007). The amount of nitrogen leached through the soil profile was similar in a forest and unfertilized lawn system at 1.4 kg/ha, compared to 6.0 kg/ha in fertilized lawns (Gold et al 1990).…”
mentioning
confidence: 99%